Knowledge in health: The optic afro- indigenous in collective health care (Research, Society and Development, 2021)
This review has to objective to interpret analyze the work, "A Ialorixá e o Pajé", by writer Maria Stella de Azevedo Santos, released in 2018 by Solisluna, from the perspective of care and interpersonal relationships between health care professionals and the care offered through of plants in indigenous and African culture. The work also discusses racism in professional relationships that health visitor Maria Stella faced in her professional career. Marked by a reading without technical terms, the book can be appreciated by health professionals, children and adolescents, readers interested in interdisciplinary care, racism and indigenous care. It adds knowledge to the area of health care, herbal medicine, racism, nursing, in addition to contributing to the search for knowledge in the culture of indigenous care. As applied methodology, it was decided to carry out an interpretive analysis of the book and its respective messages.